2013
DOI: 10.1016/j.compstruct.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on mean crushing stress characterization of carbon–epoxy plies under compressive crushing mode

Abstract: a b s t r a c tA challenge in numerical simulation of crashworthiness study is to be able to predict the crush damage modes, their evolution during crushing and the energy absorption in any composite structure from elementary material characterisation data. Therefore, it is important to know the behavior of one ply subjected to crushing load, and especially to determine the mean crushing stress that could be used for simulation. For that purpose, quasi-static crushing tests are performed for different configur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…A set of laminated wedge specimens were crush-tested by Israr et al [21] and the results were used to validate the present model. A hydraulic testing machine, at a constant crosshead displacement rate of 6mm/min was used on T700/M21 [(0°/90°) 4 ] s specimens with a 20° chamfer angle.…”
Section: Methodsmentioning
confidence: 99%
“…A set of laminated wedge specimens were crush-tested by Israr et al [21] and the results were used to validate the present model. A hydraulic testing machine, at a constant crosshead displacement rate of 6mm/min was used on T700/M21 [(0°/90°) 4 ] s specimens with a 20° chamfer angle.…”
Section: Methodsmentioning
confidence: 99%
“…Israr et al [15] showed that during crushing process, the crushing stress is about constant (Fig. 20) and its value is similar to the compressive matrix failure stress.…”
Section: Modeling In the Transverse Directionmentioning
confidence: 82%
“…(4)) could lead to high positive strain in the out-of-plane direction and to increasing of the crushing stress r crush t . But the results of Israr et al [15] showed that during crushing process, the crushing stress is about constant, then it is necessary to take into account this expansion to define the t-crushing stress:…”
Section: Modeling In the Transverse Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis predicted the crushing load but predicting the peak loads in the crushing process would require a much more refined model. The crushing of laminated plates is thought to be simpler because it involves fewer failure modes than that of laminated tubes [345][346][347][348]. Experiments showed significant differences between the static and dynamic crushing of composite materials.…”
Section: Aerospace Applicationsmentioning
confidence: 99%